2018
DOI: 10.1016/j.tafmec.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Tensile failure prediction of U-notched plates under moderate-scale and large-scale yielding regimes

Abstract: The main goal of the present research is to check if the recently published experimental results on tensile load-carrying capacity (LCC) of ductile U-notched Al 7075-T6 and Al 6061-T6 plates could successfully be predicted by means of combining the Equivalent Material Concept (EMC) with the Averaged Strain Energy Density (ASED) criterion, which is fundamentally a brittle fracture criterion. By using the two main material properties, namely the fracture toughness and the tensile strength of the equivalent mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
0
34
1
Order By: Relevance
“…As previously mentioned, the experimental results presented in Section 2 have been recently predicted theoretically in Torabi et al by means of the 2 stress‐based failure criteria, namely, the EMC‐PS and EMC‐MS criteria. Moreover, in a separate research, the experimentally obtained LCCs reported in Torabi et al have been repredicted by means of the EMC‐ASED criterion in Torabi et al Thus, 3 distinct predictions of the experimentally obtained failure loads have been reported in Torabi et al for the U‐notched plates made of Al 7075‐T6 and Al 60161‐T6 and subjected to mode I loading. In this section, a full discussion is presented about the differences between these 3 theoretical results and the results of the newly proposed EMC‐J criterion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, the experimental results presented in Section 2 have been recently predicted theoretically in Torabi et al by means of the 2 stress‐based failure criteria, namely, the EMC‐PS and EMC‐MS criteria. Moreover, in a separate research, the experimentally obtained LCCs reported in Torabi et al have been repredicted by means of the EMC‐ASED criterion in Torabi et al Thus, 3 distinct predictions of the experimentally obtained failure loads have been reported in Torabi et al for the U‐notched plates made of Al 7075‐T6 and Al 60161‐T6 and subjected to mode I loading. In this section, a full discussion is presented about the differences between these 3 theoretical results and the results of the newly proposed EMC‐J criterion.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed during the experiments that the failure in U‐notched Al 7075‐T6 specimens occurs suddenly with a moderate‐scale yielding (MSY) regime, while in Al 6061‐T6 specimens by large‐scale yielding (LSY) regime and in a stable manner . In another research, Torabi et al have re‐predicted well the tensile load‐carrying capacity (LCC) of the thin U‐notched rectangular plates tested reported in Torabi et al by linking EMC to the averaged strain energy density (ASED) criterion, called EMC‐ASED criterion. A research has been more recently performed by Torabi and Habibi on ductile failure of U‐notched Al 6061‐T6 rectangular plates under mixed mode I/II loading conditions in which failure took place by LSY regime.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, the tensile strength of the equivalent material (σ * f ) can be evaluated by the following formulation [23][24][25] : Initially, 2 assumptions have been made to formulate the elastic-plastic behaviour of a real ductile material to the linear-elastic behaviour of a virtual brittle material till the fracture moment 21 : The tensile strength of the equivalent material has been calculated by combining the power-law equation which considers plastic behaviour of the real ductile material using the stress-strain relationship and the SED formulation for brittle materials at the point when the crack growth commences.…”
Section: Equivalent Materials Conceptmentioning
confidence: 99%
“…26,27 the EMC has been linked to the MTS and MS criteria, providing the 2 ductile failure prediction models, called EMC-MTS and EMC-MS. [23][24][25] Cicero and co-researchers 16 have tested PMMA SENB weakened by U-notches and loaded under symmetric 3-point bending, experienced considerable plastic deformations around their notch border. As a successful fracture criterion, the ASED criterion has been used by some researchers to evaluate the brittle fracture of cracked and notched samples made of different brittle and quasi-brittle materials (eg, rocks, polymers, and graphite).…”
Section: Introductionmentioning
confidence: 99%